Vulvar Nonclear Cell Syringoma Associated with Pruritus and Diabetes Mellitus. (28th August 2013) - Akoglu, Gulsen; Ibiloglu, Ibrahim; Durmazlar, Nezih
Abstract : Background . Syringoma is a benign eccrine sweat gland tumor, characterized by multiple skin colored or slightly yellowish papules. Vulvar syringoma without extragenital involvement is an extremely rare variant of syringoma. Mail Observations . Herein, we report a 40-year-old diabetic female patient who presented with only lichenified plaques on the vulvar region without any extragenital lesions. Diagnosis of vulvar syringoma was made depending on the characteristic double lined cystic enlargements and comma-like tails found in histopathological examination. Immunohistochemical stains for estrogen and progesterone receptors were negative. Conclusion . Vulvar syringoma may present with no obvious papules on lichenified plaques.